2019
DOI: 10.3390/medicina55090570
|View full text |Cite
|
Sign up to set email alerts
|

Organised Versus Opportunistic Cervical Cancer Screening in Urban and Rural Regions of Lithuania

Abstract: Background and Objectives: In 2004, Lithuania started the Nationwide Cervical Cancer Screening Programme. However, screening is more opportunistic than population-wide and the programme’s coverage is insufficient. The aim of this study was to assess the effect of systematic personal invitation on coverage of cervical cancer (CC) screening in urban and rural regions of Lithuania. Materials and Methods: The study was conducted in an urban primary healthcare centre (PHCC) and in a rural PHCC, where prevailing CC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Furthermore, research and practice have shown that cervical cancer screening rate is highly correlated with mammography screening rate [ 35 ]. Our finding is consistent with that of Yang et al, Huang et al, and Paulauskiene et al who found that the coverage and participation of breast and cervical cancer screening were higher in rural regions compared to urban regions in China and Lithuania [ 38 , 39 , 40 ]. In addition, institutions in lower GDP districts showed a better screening performance than those in higher GDP districts.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, research and practice have shown that cervical cancer screening rate is highly correlated with mammography screening rate [ 35 ]. Our finding is consistent with that of Yang et al, Huang et al, and Paulauskiene et al who found that the coverage and participation of breast and cervical cancer screening were higher in rural regions compared to urban regions in China and Lithuania [ 38 , 39 , 40 ]. In addition, institutions in lower GDP districts showed a better screening performance than those in higher GDP districts.…”
Section: Discussionsupporting
confidence: 93%
“…These findings suggest that more people should be encouraged to work in the primary healthcare system, and that the training for cancer screening should be strengthened, to augment the quantity and quality of staff dedicated to cancer screenings [ 34 , 41 ]. In addition, to improve population-based cancer screening performance appropriate screening techniques should be made available, more medical resources should be introduced, and program supervision should be strengthened [ 29 , 30 , 38 ]. Finally, to identify target population who are less likely to be exposed to cancer screenings is critical to screening participation and performance.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic personal invitation for cervical cancer screening seems to be an effective form of information about screening. The one reminder letter used in Lithuania more than doubled the coverage of screening [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…An earlier Lithuanian survey found that the amount of women who had participated in the Nationwide Cervical Cancer Screening Program was lower in urban areas than in rural areas (9.6 vs. 14.7%) [ 31 ]; however, a reminder letter increased attendance to 24.6% and 30.8%, respectively. In the UK, the 5-year coverage of the Pap test rate in women ranged between 77.8%–79.0% in 2011–2012 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%